Radiation Effects in Nuclear Ceramics - L. Thomé; S. Moll; A. Debelle; F. Garrido; G. Sattonnay; J. Jagielski (Advances in Materials Science and Engineering)
Due to outstanding physicochemical properties, ceramics are key engineering materials in many industrial domains. The evaluation of the damage created in ceramics employed in radiative media is a challenging problem for electronic, space, and nuclear industries. In this latter field, ceramics can be used as immobilization forms for radioactive wastes, inert fuel matrices for actinide transmutation, cladding materials for gas-cooled fission reactors, and structural components for fusion reactors. Information on the radiation stability of nuclear materials may be obtained by simulating the different types of interactions involved during the slowing down of energetic particles with ion beams delivered by various types of accelerators. This paper presents a review of the radiation effects occurring in nuclear ceramics, with an emphasis on recent results concerning the damage accumulation processes. Energetic ions in the KeV-GeV range are used to explore the nuclear collision (at low energy) and electronic excitation (at high energy) regimes. The recovery by electronic excitation of the damage created by ballistic collisions (SHIBIEC process) is also addressed.